Kolokasi Leksikal dan Gramatikal dalam Cerpen Ahdu as-Syaitan karya Taufiq al-Hakim - Bahy Chemy Ayatuddin Assri (Alfaz (Arabic Literatures for Academic Zealots), 2022)
This paper wants to reveal the pattern of lexical and grammatical collocations in the short story Ahdu as-Syaitan by Taufiq al-Hakim by using a combination of theory between Benson and Hafidz. A collocation is a phrase consisting of words that are used together and the original meaning can be traced so that it does not create a new meaning. In the field of education, teachers tend to teach vocabulary without collocation. This is due to the teacher's lack of understanding of collocation. In the field of terjamah, often the collocation equivalent does not match the dictionary. If you want to say 'watching tv', you should use يشاهد التلفاز not ينظر التلفاز. The results of the study include: the researcher found six collocations consisting of four grammatical and two lexical collocations. The pattern used in grammatical collocations is KB + preposition in KB phrase, KK + preposition KB phrase, where the phrase is an adverb, KK + preposition of noun phrase, where the phrase is an object. The pattern used in lexical collocations is KK + adverb.